Effect of Milk Powder as A Protective Agent on the Stability of Anti-Hp-IgY - Zhang, Xiaoyuan; Jian, Xiaohong; Zhang, Zhi; Li, Zaixin (International Journal of Public Health and Medical Research, 2026)
Currently, multiple antibiotic combination therapy is predominantly used in clinical practice for the treatment of related infections. Although the cure rate is approximately 80%, drug resistance is increasing annually, the eradication efficacy is gradually declining, and long-term antibiotic use can readily lead to intestinal flora dysbiosis and functional disorders. Egg yolk immunoglobulin (IgY) has the potential to serve as an alternative to traditional antibiotic therapies due to its high specificity, ease of production, and lack of toxic side effects. In this study, milk powder was added as a protective agent to specific IgY lyophilized powder to investigate its storage stability, tolerance to pH changes and pepsin, with IgY titer changes measured using ELISA. The results showed that specific IgY retained stable titers within the pH range of 3–7.8. At pH 1, the residual activity of IgY was 43.0%, while the addition of milk powder under the same conditions increased the antibody activity retention rate to 72.3%. IgY exhibited relatively high resistance to pepsin, with a retention rate of 79.6% after 1 hour of pepsin treatment; the addition of milk powder further increased the retention rate to 88.0%. In stability experiments using milk powder as a protective agent, antibodies stored at 4°C or −20°C retained approximately 50% activity after 360 days. The results showed that Milk powder, as a natural and low-cost protective agent, effectively improves the pH stability, pepsin tolerance, and long-term storage activity of IgY. This study provides robust theoretical and data support for the development of highly effective and stable oral IgY formulations, thereby promoting their clinical translation and application in the prevention and treatment of related infections.